Penerapan Metode Scaffolding Berbantuan LKPD (Lembar Kerja Peserta Didik) untuk Meningkatkan Hasil Belajar Matematika - Aristia, Baiq Elisa; Junaidi, Junaidi; Afifah, Afifah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This research aims to improve mathematics learning outcomes through the implementation of the scaffolding method assisted by Student Worksheets (LKPD). The research method used was Classroom Action Research (CAR), conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection. The study involved 38 ninth-grade students as research subjects. Data were collected through observations and learning outcome tests. The results showed an increase in students' learning outcomes from 71% in the first cycle to 87% in the second cycle. These findings indicate that the application of the scaffolding method assisted by LKPD is effective in enhancing mathematics learning outcomes, particularly in improving conceptual understanding, critical thinking skills, and engagement in group discussions.